Inter Partner Conflicts, Social Support, Coping Skills and Perceived Stress in Pregnant Women (Journal of Asian Development Studies, 2025)
Pregnancy is a sensitive period marked by biological and psychosocial changes that may heighten stress. Inter-partner conflict is a key stressor, while social support and coping skills may buffer its effects. This study examined the relationship between inter-partner conflict, social support, coping skills, and perceived stress in pregnant women. A purposive sample of 300 women was recruited from different hospitals. Standardised tools, including the Dyadic Adjustment Scale, Perceived Stress Scale, Social Support Questionnaire, and Coping Skills Questionnaire, were used. Correlation analysis revealed that inter-partner conflict was positively associated with perceived stress (r = 0.43, p < 0.01), while social support (r = –0.23, p < 0.01) and coping skills (r = –0.14, p < 0.05) were negatively associated with stress. Regression analysis showed that social support (β = –.22, R² = .52, p < .001) and coping skills (β = –.14, R² = .30, p < .001) significantly predicted lower stress, whereas inter-partner conflict predicted higher stress (β = .10, R² = .40, p < .001). These findings highlight the importance of incorporating psychosocial screening into maternal healthcare and promoting interventions that build coping skills and enhance social support. Such measures can reduce stress and improve maternal and fatal well-being.